Notes on the Church of St Fyndoca and its Monuments, on the Island of Inishail, Loch Awe - Douglas, William (Proceedings of the Society of Antiquaries of Scotland, 1912)
It is traditionally believed that there was a nunnery on the island but there is no evidence to support this assertion. Within the churchyard there are no legible inscriptions on any of the gravestones. There is a large flat tomb which commemorates the Campbell family. The heraldic shield is supported by two warriors, and surmounted by a diadem. An erect cross-slab carved on front and back survives.